Kemampuan Motorik Halus Anak melalui Kegiatan Melipat Kertas Origami - Febriyani Harahap; Seprina (Aṭfāluna: Journal of Islamic Early Childhood Education, 2019)
The phenomenon needing to consider at this time is the lack of development of fine motor children in the daily activity. Simple things such as buttoning their clothes, combing their hair, wearing shoelaces, folding their clothes, in fact, are difficult to do for children in Taman Kanak-Kanak Raisyah Padangsidimpuan. Therefore, this study aimed to improve children's fine motor skills through folding paper origami. This type of research used classroom action research consisting of 2 cycles. The research was carried out in Taman Kanak-Kanak Raisyah Padangsidimpuan in group B with 15 children consisted of 9 boys and 6 girls. Based on the results found through observation techniques, interviews, tests, and documentation, it was concluded that folding paper origami can improve the fine motor skills of children in group B of Taman Kanak-Kanak Raisyah Padangsidimpuan. It could be seen from the achievement value in the first cycle stage only 33%. Whereas after the second cycle was done, the achievement of the value obtained reached 86%.